Biomarkers for cervical cancer screening: the role of p16INK4a to highlight transforming HPV infections - Knebel Doeberitz, Magnus von; Reuschenbach, Miriam; Schmidt, Dietmar (Expert review of proteomics, 2014)
Biomarkers indicating the initiation of neoplastic transformation processes in human papillomavirus (HPV)-infected epithelial cells are moving into the focus of cancer prevention research, particularly for anogenital cancer, including cancer of the uterine cervix. Based on the in-depth understanding of the molecular events leading to neoplastic transformation of HPV-infected human cells, the cyclin-dependent kinase inhibitor p16INK4a turned out to be substantially overexpressed in virtually all HPV-transformed cells. This finding opened novel avenues in diagnostic histopathology to substantially improve the diagnostic accuracy of cervical cancer and its precursor lesions. Furthermore, it provides a novel technical platform to substantially improve the accuracy of cytology-based cancer early-detection programs. Here, we review the molecular background and the current evidence for the clinical utility of the p16INK4a biomarker for HPV-related cancers, and cervical cancer prevention in particular.